Ising Model in Human Social Interaction; The Physics Application Theory in Social Field - Yulia Zahra (ADALAH, 2019)
AbstractPhysics as a natural science is very wide. One of the intriguing topics which were so famous in 1925 is the Ising Model. This model describes the interaction of spins in lattices. A spin is an intrinsic form of angular momentum carried by elementary particles. Elementary particles are very tiny which composed a body. In reality, they always interact with each other and their interactions are so complicated. If we connect this phenomenon with social interaction, where all human beings in daily life always interact with each other. This is an extraordinary fact, that not only humans always interact as social creatures, but also elementary particles interact with each other and the environment around them.Keywords: Ising Model, social creatures, interaction AbstrakFisika sebagai ilmu alam sangat luas. Salah satu topik menarik yang sangat terkenal pada tahun 1925 adalah Ising Model. Model ini menggambarkan interaksi spin dalam kisi. Spin adalah bentuk intrinsik dari momentum sudut yang dibawa oleh partikel elementer. Partikel-partikel elementer sangat kecil yang membentuk suatu benda. Pada kenyataannya mereka selalu saling berinteraksi dan intereksinya sangat rumit. Jika kita menghubungkan fenomena ini dengan interaksi sosial, di mana semua manusia dalam kehidupan sehari-hari selalu saling berinteraksi. Ini adalah fakta yang luar biasa, bahwa tidak hanya manusia selalu berinteraksi sebagai makhluk sosial, tetapi juga partikel elementer berinteraksi satu sama lain dan lingkungan di sekitar mereka.Kata kunci: Ising Model, makhluk sosial, interection